Micro and Precision Manufacturing (Engineering Materials,, 2018)
This book provides details on various micro and precision manufacturing and finishing operations performed by conventional and advanced processes, including micro-manufacturing of micro-tools and precision finishing of engineered components. It describes the process mechanism, principles and parameters while performing micro-fabrication and precision finishing operations. The text provides the readers with knowledge of micro and precision manufacturing and encourages them to explore the future venues in this field.